Structure and gene cluster of the o–antigen of Escherichia coli o96. (February 2016) - Guo, Xi; Senchenkova, Sof'ya N.; Shashkov, Alexander S.; Perepelov, Andrei V.; Liu, Bin; Knirel, Yuriy A.
Highlights: Chemical structure of the O96 polysaccharide was established. The O-antigen gene cluster includes seven genes and is located between galF and gnd . The O96-antigen structure and gene cluster are similar to those of E. coli O170. Graphical abstract: Abstract: Mild acid degradation of the lipopolysaccharide of Escherichia coli O96 afforded a mixture of two polysaccharides. The following structure of the pentasaccharide repeating unit of the major polymer was established by sugar analysis, Smith degradation, and 1 H and 13 C NMR spectroscopy: The O-antigen gene cluster of E. coli O96 between conserved galF and gnd genes was found to be consistent with this structure, and hence, the major polysaccharide represents the O96-antigen. The O96-antigen structure and gene cluster are similar to those of E. coli O170, and two proteins encoded in the gene clusters of both bacteria were putatively assigned a function of galactofuranosyltransferases. The minor polymer has the same structure as a peptidoglycan-related polysaccharide reported earlier in Providencia alcalifeciens O45 and several other O-serogoups of this species (Ovchinnikova OG, Liu B, Kocharova NA, Shashkov AS, Kondakova AN, Siwinska M, Feng L, Rozalski A, Wang L, Knirel YA. Biochemistry (Moscow) 2012;77 :609-15) →4)-β-d -Glc p NAc-(1→4)-β-d -Glc p NAc3( R lac-l Ala)-(1→ where R lac-l Ala indicates ( R )-1-[( S )-1-carboxyethylaminocarbonyl]ethyl.